Arterial Infusion Chemotherapy for Neoplastic Esophagogastric Anastomotic Strictures After Esophagectomy - Xie, Pengfei; Yin, Meipan; He, Wei; Ma, Yaozhen; Li, Chunxia; Li, Zhen; Li, Xiaobing; Wang, Shuai; Wu, Gang (Frontiers in Oncology, 2021)
Background: Neoplastic esophagogastric anastomotic strictures after resection of esophageal cancer is a very difficult problem in clinical practice. We aim at to investigate the safety and feasibility of arterial infusion chemotherapy in treatment of neoplastic esophagogastric anastomotic strictures after esophagectomy. Methods: From October 2014 to December 2019, 50 patients with Neoplastic esophagogastric anastomotic strictures after resection of esophageal cancer were assessed retrospectively. Preoperative dysphagia was grade III in 34 cases and grade IV in 16 cases. Thirty-eight patients had different degrees of dyspnea before surgery Twenty-five patients had intolerable (grade IV) dyspnea and airway stenting was undertaken before surgery. Thirteen patients had tolerable dyspnea that did not require airway stenting, and preoperative dyspnea was grade III. Results: All patients were successfully treated with arterial infusion chemotherapy, no paraplegia or death occurred. The dysphagia grade of 50 patients after AIC was compared: one case had grade I, 40 cases had grade II, and nine cases had grade III. Thirteen patients had tolerable dyspnea that did not necessitate airway stenting. Dyspnea was classified as grade I in five cases and grade II in eight cases. After 1–3 courses of AIC, 50 patients were followed up for a complete response (eight cases), partial response (28) and stable disease (14 cases). Total objective effective rate (complete response+ partial response) and disease control rate(complete response + partial response＋stable disease)were 72.0% and 100.0%, respectively.The median duration of follow-up was 8.5 months. One-year survival was 46.0%. Conclusion: arterial infusion chemotherapy is safe and efficacious treatment for Neoplastic esophagogastric anastomotic strictures after esophagectomy.